Parental dental anxiety levels in pediatric dentistry - KOL DOāžAN, Åžebnem; ÇELENK, Sema (Conservative Dentistry Journal, 2023)
Background: Dental anxiety is defined as the apprehension and fear of terrible events occurring during dental treatment, coupled with a sense of losing control. There are numerous individual and environmental factors causing dental anxiety in children, with the most significant environmental factor being the family environment in which the child is raised. Purpose: To break a possible cycle of dental anxiety within families, it may be necessary to assess and particularly address the level of dental anxiety in parents, especially mothers. In eliminating dental anxiety, providing parents with information to reduce their dental worries and teaching them coping strategies will be a significant step in minimizing the impact of these anxieties on their children.Reviews: The fears related to dental treatments of parents and/or siblings can induce dental anxiety in children. Studies have found that children with odontophobic parents are more likely to develop odontophobia. Additionally, research results indicate that dental anxiety can be transmitted among family members through modeling.Conclusion: Our literature review indicates that dental anxiety is significantly widespread among both children and adults in society. The observation that children with parents who suffer from dental anxiety tend to have a higher level of dental anxiety themselves suggests that resolving this issue should begin with the parents.